A new model characterizing the fatigue delamination growth in DCB laminates with combined effects of fiber bridging and stress ratio. (15th July 2021) - Jiang, Linfei; Zhang, Yongxiang; Gong, Yu; Li, Wangchang; Ren, Sue; Liu, Hao
Abstract: For composite multidirectional laminates widely used in engineering, there is still no effective model to characterize the fatigue delamination behavior with the combined effects of fiber bridging and stress ratio. A new fatigue delamination model was thus proposed in this study to deal with this problem. The model was established based on the fatigue driving force and fatigue delamination resistance, which characterized the effects of stress ratio and fiber bridging, respectively. A series of mode I fatigue delamination tests on composite multidirectional laminates were conducted under various stress ratios (0.1, 0.3 and 0.5) and different pre-crack lengths. Both the experimental results of this study and public fatigue data from laminates with other materials and various interfaces showed that a single master curve with a narrow band can be obtained by using the new model for all fatigue data under different stress ratios and fiber bridging effects. In addition, the determined model parameters obtained from fatigue data under specific stress ratios were used for predicting the fatigue delamination behavior under other stress ratios. Good agreements between the predictions and experimental results can be achieved, which further indicated the model's applicability.